Quercetin and lipoate effect on the glutathione system in retina in terms of diabetes simulation - O.A. Moroz (Ukrainian Society of Ophthalmologists, 2015)
The relevance of the work lies in the research of the quercetin and lipoate effect in terms of experimental diabetes treatment. Objective. To study the quercetin and lipoate effect on the glutathione system in retina in terms of diabetes progress process (in two and six months). Materials and methods. The research was conducted using albino rats. Experimental animals were divided into four groups: the first one - control group (14 rats); the second one - experimental group (14 rats), untreated animals with developing diabetes; the third one - experimental group (12 rats), animals with developing diabetes and lipoic acid administration; the fourth one - experimental group (15 rats), animals with developing diabetes and quercetin administration. Reduced and oxidized glutathione content was determined in retinal homogenates. Results. Lipoic acid and quercetin use enhanced the reduced glutathione level by 107.2 and 84.3% in 2 months in terms of research, and by 134.8% and 113.0 in 6 months after the diabetes progress compared to the group of untreated animals. Conclusion. In terms of streptozotocin-induced diabetes progress the decrease of coenzyme (reduced) glutathione form by 61.9% (in 2 months) and by 68.3% (in 6 months) was determined. Lipoic acid and quercetin medical products administration had a normalizing effect on the retinal metabolism, which is manifested in the reduced glutathione levels increase by 107.2 and 84.3% (in 2 months) and by 134.8 and 113.0% (in 6 months). The lipoic acid application creates a more distinct normalizing effect on the glutathione level.